Manufacturing Organic Fertilizer By A Group Of Farmer Households In Sungai Rengas Village Kubu Raya District - Sri Rahayu; Setiawan Setiawan; F Tamtomo (STKIP Singkawang, 2022)
Currently, there are many organic fertilizers sold in the market, but it is no less important that housewives farmers can make their own, in order to take advantage of the waste that is around their household. The purpose of this activity is that household waste that exists in each household can be used as a useful material for crops that are planted in their gardens or in their yard. This activity is a collaboration between the faculty and independent farmers engaged in organic vegetable entrepreneurship which will be carried out in September 2021, which was followed by women farmers who were in Sungai Rengas village, Kubu Raya Regency. The method used in this activity consisted of lectures and demonstrations, as well as evaluation. The results of this activity were very enthusiastic, because all this time they considered that the waste in the household was only waste or garbage. The results of the evaluation that the fertilizer made by the women were very good, which was shown by after being applied to the flower cabbage plant.